Acute Renal Failure Due to Acute Tubular Necrosis Caused by Direct Invasion of Orientia tsutsugamushi - Kim, Dong-Min (American Society for Microbiology (ASM), 2008)
We describe a scrub typhus patient with acute renal failure for whom a diagnosis was made based on serology as well as immunohistochemical (IHC) staining and an electron microscopic examination (EM) of a renal biopsy specimen. For our case, we demonstrated by IHC staining and EM that renal failure was caused by acute tubular necrosis due to a direct invasion of Orientia tsutsugamushi.